Certified Reference Materials of Molybdenum Ore and Molybdenum Concentrate (GBW07141, GBW07142, GBW07143 and GBW07144). Issue 4 (29th June 2018) - Liu, Mei; Cheng, Zhizhong; Huang, Hongku; Gu, Tiexin; Yan, Weidong; Wang, Lijun; Bai, Jinfeng
Abstract : This study describes the preparation and characterisation of certified reference materials of three molybdenum ores (GBW07141 to GBW07143, abbreviated to GMo‐1 to GMo‐3) and one molybdenum concentrate (GBW07144, abbreviated to GMo‐4). The source of these materials was molybdenum deposits in Luanchuan in Henan Province, China. Sample homogeneity was tested by WD‐XRF. All the relative standard deviations were < 3.0%, and F ‐tests showed that all four materials were homogeneous. Thirteen laboratories participated in this interlaboratory programme, and to set the values, various reliable analytical methods based on different principles were adopted. Up to twenty‐six elements and compounds in the three molybdenum ores and eighteen components in the molybdenum concentrate were characterised as certified values. Owing to the wide spread of the data, only indicative values could be obtained for Ag and Re in GMo‐1 and for nine components in GMo‐4. The certified values and uncertainties for Mo of the three molybdenum ores and the molybdenum concentrate were, respectively, 0.066 ± 0.003, 0.15 ± 0.01, 0.54 ± 0.02 and 50.08 ± 0.14% m/m . Key Points: Three Mo ores and one Mo concentrate were prepared and characterised as CRMs in a thirteen‐laboratory programme. Twenty‐six and eighteen analytes in the ores and concentrate respectively were assigned certified values. Certified values and uncertainties for Mo in the ores and concentrate were 0.066 ± 0.003, 0.15 ± 0.01, 0.54 ± 0.02 and 50.08 ± 0.14% m/m . respectively.